The language animal the full shape of the human linguistic capacity - Taylor, Charles 1931- (<<The>> Belknap Press of Harvard University Press, 2016)
"In this book, Charles Taylor explains linguistic holism to people who believe language needs to be thought of as bits of information. According to one influential view of language, one that originated with Hobbes, Locke, and Condillac, language serves to encode information and to communicate it. This theory has been rendered more sophisticated over the last two centuries, but it still gives a central place to the encoding of information. The thesis of Taylor's new book is that this view neglects crucial features of our language capacity. Sometimes language serves not just to encode information, but also shapes what it purports to describe. This language is more than merely 'descriptive;' it plays a 'constitutive' role."...Provided by publisher
Keywords: Linguistik; Philosophie; Sprache; Language and languages -- Philosophy; Linguistics -- Philosophy; Cognition; Biolinguistik; Kognitive Linguistik; Sprachphilosophie; Sprachursprung